Calpain-1 ablation partially rescues disease-associated hallmarks in models of Machado-Joseph disease. (21st January 2020) - Weber, Jonasz J; Haas, Eva; Maringer, Yacine; Hauser, Stefan; Casadei, Nicolas L P; Chishti, Athar H; Riess, Olaf; Hübener-Schmid, Jeannette
Abstract: Proteolytic fragmentation of polyglutamine-expanded ataxin-3 is a concomitant and modifier of the molecular pathogenesis of Machado–Joseph disease (MJD), the most common autosomal dominant cerebellar ataxia. Calpains, a group of calcium-dependent cysteine proteases, are important mediators of ataxin-3 cleavage and implicated in multiple neurodegenerative conditions. Pharmacologic and genetic approaches lowering calpain activity showed beneficial effects on molecular and behavioural disease characteristics in MJD model organisms. However, specifically targeting one of the calpain isoforms by genetic means has not yet been evaluated as a potential therapeutic strategy. In our study, we tested whether calpains are overactivated in the MJD context and if reduction or ablation of calpain-1 expression ameliorates the disease-associated phenotype in MJD cells and mice. In all analysed MJD models, we detected an elevated calpain activity at baseline. Lowering or removal of calpain-1 in cells or mice counteracted calpain system overactivation and led to reduced cleavage of ataxin-3 without affecting its aggregation. Moreover, calpain-1 knockout in YAC84Q mice alleviated excessive fragmentation of important synaptic proteins. Despite worsening some motor characteristics, YAC84Q mice showed a rescue of body weight loss and extended survival upon calpain-1 knockout. Together, our findings emphasize the general potential of calpains as a therapeutic target in MJD and other neurodegenerative diseases.